Occult Hepatitis B Virus Infection among HIV Positive Patients in Nigeria - Opaleye, Oluyinka Oladele (Hindawi Publishing Corporation, 2014)
HIV has been known to interfere with the natural history of hepatitis B virus (HBV) infection. In this study we investigate the prevalence of occult hepatitis B virus infection (OBI) among HIV-infected individuals in Nigeria. Overall, 1200 archived HIV positive samples were screened for detectable HBsAg using rapid technique, in Ikole Ekiti Specialist Hospital. The HBsAg negative samples were tested for HBsAg, anti-HBc, and anti-HCV by ELISA. Polymerase chain reaction was used for HBV DNA amplification and CD4 counts were analyzed by cytometry. Nine hundred and eighty of the HIV samples were HBsAg negative. HBV DNA was detected in 21/188 (11.2%) of patients without detectable HBsAg. CD4 count for the patients ranged from 2 to 2,140 cells/μL of blood (mean = 490 cells/μL of blood). HCV coinfection was detected only in 3/188 (1.6%) of the HIV-infected patients (P > 0.05). Twenty-eight (29.2%) of the 96 HIV samples screened were positive for anti-HBc. Averagely the HBV viral load was <50 copies/mL in the OBI samples examined by quantitative PCR. The prevalence of OBI was significantly high among HIV-infected patients. These findings highlight the significance of nucleic acid testing in HBV diagnosis in HIV patients.